Effect of yogasana and aerobic exercise on selected physical variables of university women students / G .Vasanthi - G., Vasanthi (Faculty of Sports Science and Recreation, 2013)
The aim of this study is to determine the effect of yoga asana and aerobic exercises on selected physical fitness variables of university women students. Thirty healthy, untrained women subjects were selected from the hostels of Pondicherry University and their age ranged from 20 to 25 years. The subjects were equally divided into three groups namely control and two experimental groups. Control group (Group I) did not undergo any training programme rather than their daily routine work. The experimental group (Group II) underwent yoga asana practice and (Group III) were treated with aerobic exercises for forty five minutes duration for twelve weeks except Saturday and Sunday. Static balance and flexibility were measured through field tests. The flexibility and static balance was measured before and after the completion of yoga asana practice and aerobic training. The results of pre-test and post-test were statistically analyzed by using Analysis of Co-variance. The result revealed that flexibility and static balance had significant improvement due to the practices of yoga asana and aerobic training when compared to the control group. The result when compared between the two experimental groups revealed that the yoga asana group had significant effect on flexibility and static balance than the aerobic group.